Development of Nonketotic Hyperglycemia Requiring High-Dose Insulin After Supratherapeutic Amlodipine Ingestion - Nishant Kumar, DO, MS; Mihail Zilbermint, MD, MBA, FACE (AACE Clinical Case Reports, 2024)
Background/Objective: Calcium channel blockers, when taken in overdose quantities, can cause hyperglycemia requiring so-called hyperinsulinemic-euglycemic therapy. The objective of this report was to describe a patient with calcium channel blocker toxicity resulting from overdose of amlodipine. Case Report: A 74-year-old man presented with a fall and loss of consciousness. Prior to this event, he consumed 88 tablets of amlodipine. Medical history was significant for hypertension, hyperlipidemia, and cerebrovascular accident. His vital signs were heart rate of 51 beats/min, blood pressure of 162/137 mm Hg, oxygen saturation of 94% on room air, and respiratory rate of 16 breaths/min. The patient soon became hypotensive. The blood glucose level was 227 mg/dL. Urinalysis was negative for ketones. The patient was diagnosed with calcium channel blocker toxicity and admitted to the intensive care unit. He received continuous insulin infusion and dextrose 25% in water for 5 and 7 days respectively, with a peak insulin infusion rate of 850 U/h. After discontinuation of medications, the glucose level, blood pressure, and heart rate were 82 mg/dL, 127/68 mm Hg, and 86 beats/min, respectively, and he returned to prior functional status. Discussion: Amlodipine is a long-acting dihydropyridine class calcium channel blocking drug. In the overdose setting, amlodipine inhibits calcium uptake by myocytes and release of insulin from pancreatic beta cells. Conclusion: In this case, high-dose insulin euglycemic therapy was effective in the treatment of amlodipine overdose and should be considered in similar cases.